Analisis faktor-faktor yang mempengaruhi keberfungsian pasca gempa dan tsunami di nanggroe aceh darussalam - Siti Maryam; Dadang Sukandar; Suprihatin Guhardja; Pang S. Asngari; Euis Sunarti (Media Gizi dan Keluarga, 2008)
ABSTRACT. In the end of December 2004, earthquake and tsunami disaster attacked Nanggroe Aceh Darussalam Province and North Sumatera. The disaster caused : (a) the human victims with large numbers; (b) the paralyzed of basic community services; (c) disfunction of basic infra structure; as well as (d) the destroyed of social and economic system. The objectives of this research wass to analyze the coping strategies of families after earthquake and tsunami disaster in Nanggroe Aceh Darussalam Province. This research used cross-sectional design study, it’s was performed since May 2006 in Kuta Alam and Meuraxa sub-districts. Number of samples were 138 families, which consist of 103 intact families, 20 widower families and 15 widow families. Sampling technique used proportional random sampling. Data was taken by using questionnaire. Meanwhile, both coping problem-based strategy (44.2%) and emotion-based strategy (18.1%) of families applied with degree of high level. Most of families were categorized into high category for expressive and instrumental. The significant variables which influenced the family’s expressive function were personality, widower typologi, seeking social support, planful problem solving and widows typology. Meanwhile, the variables influenced significantly on family’s instrumental function were health problem, housing problem, educational problems, plantful problem solving, self controlling, family size, social support.Keywords: coping strategies, family, earthquake and tsunami disaster